AKT Inhibitors: New Weapons in the Fight Against Breast Cancer? - Martorana, Federica; Motta, Gianmarco; Pavone, Giuliana; Motta, Lucia; Stella, Stefania; Vitale, Silvia Rita; Manzella, Livia; Vigneri, Paolo (Frontiers in Pharmacology, 2021)
The serine/threonine kinase AKT is a key component of the PI3K/AKT/mTOR signaling pathway as it exerts a pivotal role in cell growth, proliferation, survival and metabolism. Deregulation of this pathway is a common event in breast cancer including hormone receptor-positive (HR+) disease, HER2-amplified and triple negative tumors. Hence, targeting AKT represents an attractive treatment option for many breast cancer subtypes, especially those resistant to conventional treatments. Several AKT inhibitors have been recently developed and two ATP-competitive compounds, capivasertib and ipatasertib, have been extensively tested in phase I and II clinical trials either alone, with chemotherapy or with hormonal agents. Additionally, phase III trials of capivasertib and ipatasertib are already under way in HR+ and triple negative breast cancer. While the identification of predictive biomarkers of response and resistance to AKT inhibition represents an unmet need, new combination strategies are under investigation aiming to boost the therapeutic efficacy of these drugs. As such, trials combining capivasertib and ipatasertib with CDK4/6 inhibitors, immune checkpoint inhibitors and PARP inhibitors are currently ongoing. This review summarizes the available evidence on AKT inhibition in breast cancer, reporting both efficacy and toxicity data from clinical trials along with the available translational correlates and then focusing on the potential use of these drugs in new combination strategies.